2012
DOI: 10.1111/j.1948-7134.2012.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of landscape disturbance on mosquito community composition in tropical Australia

Abstract: Emerging infectious diseases are considered to be a growing threat to human and wildlife health. Such diseases might be facilitated by anthropogenic land-use changes that cause novel juxtapositions of different habitats and species and result in new interchanges of vectors, diseases, and hosts. To search for such effects in tropical Australia, we sampled mosquito populations across anthropogenic disturbance gradients of grassland, artificial rainforest edge, and rainforest interior. From >15,000 captured mosqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 26 publications
5
38
0
Order By: Relevance
“…A study similar to ours in disturbed landscapes of Australia (Steiger et al 2012) reported few differences in mosquito communities in grasslands vs. forest edges but showed that forest interiors had different mosquito composition. It may be that mosquitoes such as Cx.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…A study similar to ours in disturbed landscapes of Australia (Steiger et al 2012) reported few differences in mosquito communities in grasslands vs. forest edges but showed that forest interiors had different mosquito composition. It may be that mosquitoes such as Cx.…”
Section: Resultsmentioning
confidence: 87%
“…Anthropogenic landscape disturbance is considered a major factor in the emergence or increased transmission of zoonotic pathogens (Daszak et al 2000, Patz et al 2004, Steiger et al 2012. Invasive plants, which are frequently associated with landscape disturbance, have been shown to affect pathogen transmission potential by altering local distribution and abundance of vectors or hosts (Allan et al 2010, Reiskind et al 2010.…”
mentioning
confidence: 99%
“…; Steiger et al . ). However, the relative contributions of these factors to parasite prevalence and distribution patterns may differ substantially among parasite genera as well as among host species and populations.…”
Section: Introductionmentioning
confidence: 97%
“…First, forest edges dramatically increase in fragmented landscapes [10]. These rapidly expanding edge environments juxtapose dense rainforest with open pasture or cropland and provide opportunities for vectors or hosts to move between habitats, increasing their potential disease exposure through novel species interactions [11], [12]. Second, the replacement of rainforests with anthropogenic lands has been shown dramatically to increase the abundance of open-habitat preferring mosquitoes such as Anopheles , thereby elevating the probability of disease transmission via an increase in vectors [13][15].…”
Section: Introductionmentioning
confidence: 99%